Isolasi dan Identifikasi Bakteri Lamun Enhalus Acoroides Di Perairan Pasarwajo Buton - Sabaniah Indjar Gama; Nursiah La Nafie; Seniwati Dali (Journal of Tropical Pharmacy and Chemistry, 2015)
This research aims to isolation bacteria in segrass Enhalus acoroides 1) determination optimum growth factor of bacteria that symbiont in seagrass 2) identification kind of bacteria that isolated in seagrass. Base on the research that has done, the results show that bacteria symbiotically in seagrass grow in optimum temperature is 27 Â°C in 10-3 dilution. Identification characteristic, morphology and gram colouring bacteria that symbionts in seagrass is gram negatif bacteria that showed with result of PCR which species isolated in seagrass is enterobacter cloaceae.